CEU Graduation Ceremony 2002 - Part 3
Recording of CEU’s 11th Graduation Ceremony on June 20, 2002. The ceremony continues with the conferring of the master’s and doctoral degrees, as well as the special departmental awards. Participants: Yehuda Elkana (Rector and President of CEU), George Soros (Founder of CEU and Chairman of the Board of Trustees), the Heads of the CEU Departments, the supervisors and the PhD Candidates.